Phase 2 trial of neoadjuvant chemotherapy and transoral endoscopic surgery with risk‐adapted adjuvant therapy for squamous cell carcinoma of the head and neck. Issue 14 (9th May 2018) - Weiss, Jared M.; Grilley‐Olson, Juneko E.; Deal, Allison Mary; Zevallos, Jose P.; Chera, Bhishamjit S.; Paul, Jennifer; Knowles, Mary Fleming; Usenko, Dmitriy; Weissler, Mark C.; Patel, Samip; Hayes, David N.; Hackman, Trevor
Abstract : BACKGROUND: The objective of this study was to demonstrate the feasibility and efficacy of induction chemotherapy, surgery, and pathology‐guided adjuvant therapy to treat transorally resectable squamous head and neck cancer. METHODS: Patients had squamous head and neck cancer that was resectable by the transoral route and advanced‐stage disease (American Joint Committee on Cancer stage III‐IV, T3‐T4 tumors, and/or positive lymph nodes). They received treatment with weekly carboplatin at an area under the curve of 2, plus paclitaxel 135 mg/m 2, and daily lapatinib 1000mg for 6 weeks followed by surgical resection. Pathology that revealed margins <5 mm, extracapsular extension, N2a of N2b lymph node status, perineural invasion, or lymphovascular space invasion resulted in adjuvant radiotherapy concurrent with weekly cisplatin. Pathology with N2c/N3 lymph node status or positive margins resulted in radiation with bolus cisplatin. The primary endpoint was the clinical response rate to induction chemotherapy, and a key secondary endpoint was feasibility. RESULTS: Toxicity was modest, and 37 of 40 patients completed study procedures as planned. The clinical response rate was 93%, the pathologic complete response rate was 36%, and the clinical response did not predict for a pathologic complete response. No patient on study follow‐up has recurred or died. Twenty‐nine of 39 patients who underwent surgery avoided radiation. Speech and swallowing function were well preserved. CONCLUSIONS: The study met both its primary efficacy endpoint and the secondary feasibility endpoint. Neoadjuvant, systemic therapy and surgical resection followed by risk‐adapted adjuvant therapy resulted in high response rates and excellent long‐term outcomes and should be further studied. Cancer 2018;124:2986‐92 . © 2018 American Cancer Society . Abstract : In the context of a phase 2 study, patients with locally advanced, transorally resectable squamous cell carcinoma of the head and neck receive 6 weeks of induction chemotherapy with carboplatin, paclitaxel, and lapatinib. This is followed by surgical resection and then risk‐adapted adjuvant therapy based on the pathology report.